AB1174 TRACKING THE EFFECTS ON A CLINICAL SERVICE OF INTRODUCING ULTRASOUND FOR DIAGNOSIS OF GIANT CELL ARTERITIS: DESIGN OF A SERVICE EVALUATION USING LEAN METHODOLOGY. (2nd June 2020) - Mackie, S.; Barr, A.; Cracknell, A.; Farrell, S.; Parvin, J.; Patil, A.; Simmons, I.; Smith, K.; Sweeting, A.; Troxler, M.; Webster, T.; Wakefield, R.
Abstract : Background: In our large, multi-site hospital, patients with suspected GCA are started promptly on high-dose prednisolone but until 2019, patients waited for temporal artery biopsy (TAB) until the GCA diagnosis could be confirmed ("GCA") or refuted ("not-GCA"). Reports of the impact of introducing temporal and axillary artery ultrasound (TAUS) have mainly come from smaller hospitals. Agreement between TAUS and TAB has been reported by others with a Cohen's kappa of 0.35 [1] and 0.40 [2]. We used Lean methodology to identify metrics across 5 key domains: delivery, quality, service, morale and cost. Objectives: To design metrics for a service evaluation to measure impact of introducing TAUS, and to test their feasibility of measurement within routine care. Methods: Our primary driver was time from presenting to our service to diagnostic confirmation (lead time). Pathway mapping, value stream mapping and a driver diagram identified key ideas for improvement. We chose to measure: Delivery (mean lead time for each month), Quality (proportion of patients with GCA and positive TAB/TAUS; total (cumulative) prednisolone dose in patients with not-GCA, Service (patient feedback), Morale (staff feedback) and Cost (number of patients; cost of tests per patient; overall costs). We plotted these by month on run charts and defined a significant shift as 6 consecutive monthly values below baseline median. Cohen's kappa was calculated using GraphPad QuickCalcs. Results: Routine TAUS for suspected GCA was introduced from January 2019, alongside a multidisciplinary team monthly meeting. TAUS was done a median of 2.5 days from referral. Agreement between TAB and TAUS results was good (Table 1 ). The run chart showed a significant shift in our Delivery (median lead time fell from 28.7 days to 21 days after introduction of ultrasound) and both Quality metrics (proportion of GCA with positive TAB/TAUS increased from 29% to 69%; total prednisolone dose for not-GCA fell from 1.335g to 0.846g). Within Costs, average per-patient costs of TAB/TAUS declined from £1004/patient to £792/patient, but total referrals for TAB/TAUS increased from 6/month to 10/month, increasing overall costs. Staff and patient feedback (Service, Morale) revealed that further improvements to the care pathway were needed to manage the additional complexity. Conclusion: Lean methodology identified multiple metrics for evaluating the impact of TAUS on our service. Introducing TAUS improved Delivery and Quality, but measuring Costs, Morale and Service helped identify unintended consequences. Concordance between TAUS and TAB was good. We plan to continue to improve and monitor the care pathway based on our multi-stakeholder feedback. References: [1]Luqmani et al., HTA 2016 [2]Mukhtyar et al., Clin Rheum 2019 Disclosure of Interests: Sarah Mackie Grant/research support from: Roche (attendance of EULAR 2019; co-applicant on research grant), Consultant of: Sanofi, Roche/Chugai (monies paid to my institution not to me), Andrew Barr: None declared, Alison Cracknell: None declared, Shannon Farrell: None declared, Jimmy Parvin: None declared, Ajay Patil: None declared, Ian Simmons: None declared, Kate Smith Grant/research support from: Medical education grants from Sanofi and Biogen, Speakers bureau: Novartis, Andrea Sweeting: None declared, Max Troxler: None declared, Tara Webster: None declared, Richard Wakefield Speakers bureau: Novartis, Janssen, GE